Chronic active and chronic inactive hepatitis B virus infection: Comparative study of genetic polymorphism and blood profile measures. - Khalid Elyass Awadelkarim; Najem Aldin M Osman; A M S Eleragi; Abdelsalam M A Nail; Nadir Abuzeid; Mohamed E Elangeeb; Elsadig Mohamed Ahmed; Jaber Ahmed Al-Faifi; Abdullah Alhalafi; Ahmed S Doghish; Osama A Mohammed (PLoS ONE)
Introduction Hepatitis B virus (HBV) is a significant cause of chronic hepatitis, leading to liver complications such as cirrhosis and hepatocellular carcinoma. Toll-like receptors (TLRs) are critical in the immune response to HBV. This study investigates the TLR3 1377 C/T polymorphism's association with clinical outcomes in chronic hepatitis B patients. Materials and methods A case-control study included 136 participants (66 cases and 70 controls). The patients were categorized as having chronic active or inactive hepatitis B based on serological, biochemical, and molecular parameters. TLR3 1377 C/T polymorphism was analyzed using PCR-RFLP. The correlation between TLR3 genotypes, HBeAg status, liver enzyme levels (ALT and AST), and symptomatic presentation was assessed. Results Among the 66 cases, the CC genotype was more frequent in males with chronic active hepatitis (14 males, 5 females), but no significant gender-based difference was observed in genotype distribution. A significant association was found between the CC genotype and symptomatic presentation in chronic active cases (P = 0.015). However, no significant association was detected between TLR3 genotypes and HBeAg status (P > 0.05). Elevated ALT and AST levels were more prevalent in chronic active cases. Conclusions The TLR3 1377 C/T polymorphism, particularly the CC genotype, may influence the clinical presentation of chronic hepatitis B, particularly in symptomatic cases. However, its impact on HBeAg status and overall chronicity appears limited. Further studies are needed to clarify the role of TLR3 polymorphisms in HBV pathogenesis and their potential as therapeutic targets.